2020
DOI: 10.1002/mus.27111
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and electrophysiological examination of pinch strength in patients with amyotrophic lateral sclerosis

Abstract: Florbetapir and 18F-FDG PET/CT in systemic immunoglobulin light chain amyloidosis involving the peripheral nerves. Clin Nucl Med. 2016; 41(2):e115-e117.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Therefore, muscle strength is a critical outcome measure used in clinical trials to diagnose and assess ALS progression. [59][60][61] In rodent models, assessing grip strength provides a straightforward means of determining changes in muscle strength as ALS progresses. This assessment is often called the paw grip endurance (PaGE) test.…”
Section: Grip Strength Assessment Of Hindlimbsmentioning
confidence: 99%
“…Therefore, muscle strength is a critical outcome measure used in clinical trials to diagnose and assess ALS progression. [59][60][61] In rodent models, assessing grip strength provides a straightforward means of determining changes in muscle strength as ALS progresses. This assessment is often called the paw grip endurance (PaGE) test.…”
Section: Grip Strength Assessment Of Hindlimbsmentioning
confidence: 99%
“…Split hand, characterized by preferential weakness and wasting of the abductor pollicis brevis (APB) and first dorsal interosseous (FDI) muscles with relative sparing of the abductor digiti minimi muscle (ADM), has showed good sensitivity and specificity in the differential diagnosis of ALS (Figure 1). 3 Besides, split plus sign, 4 split pinch grip strength, 5 and split elbow 6 have been observed by both clinical assessment of muscle strength and electrophysiological studies in ALS patients. Through comparing pairs of muscle groups in a large ALS cohort, Ludolph et al found that the muscles known to receive the more pronounced corticomotoneuronal (CM) connections was significantly weaker.…”
Section: Introductionmentioning
confidence: 97%